Advanced Strategies for Enhancing the Biocompatibility and Antibacterial Properties of Implantable Structures - Mishchenko, O. M.; Volchykhina, K. P.; Maksymov, D. Ya.; Manukhina, O. M.; Pogorielov, M.; Pavlenko, M.; Iatsunskyi, I.; Міщенко, Олег Миколайович; Волчихіна, Крістіна Петрівна; Максимов, Денис Янович; Манухіна, Олеся Миколаївна (My University, 2025)
This review explores the latest advancements in enhancing the biocompatibility and antibacterial properties of implantable structures, with a focus on titanium (Ti) and its alloys. Titanium implants, widely used in dental and orthopedic applications, demonstrate excellent mechanical strength and biocompatibility, yet face challenges such as peri-implantitis, a bacterial infection that can lead to implant failure. To address these issues, both passive and active surface modification strategies have been developed. Passive modifications, such as altering surface texture and chemistry, aim to prevent bacterial adhesion, while active approaches incorporate antimicrobial agents for sustained infection control. Nanotechnology has emerged as a transformative tool, enabling the creation of nanoscale materials and coatings like TiO2 and ZnO that promote osseointegration and inhibit biofilm formation. Techniques such as plasma spraying, ion implantation, and plasma electrolytic oxidation (PEO) show promising results in improving implant integration and durability. Despite significant progress, further research is needed to refine these technologies, optimize surface properties, and address the clinical challenges associated with implant longevity and safety. This review highlights the intersection of surface engineering, nanotechnology, and biomedical innovation, paving the way for the next generation of implantable devices.
Keywords: osseointegration; titanium implants; peri-implantitis; surface modification; bacterial contamination; biocompatibility; plasma electrolytic oxidation (PEO); ion implantation; antibacterial surfaces